Sosialisasi Deteksi Dini dan Pengenalan Gejala Stadium Awal dan Akhir Kanker Serviks di Kecamatan Cinere: Indonesia - Hardini, Niniek; Rifkia, Via; Wahyuni, Yosha Putri; Sukrisno, Adi (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Cervical cancer is a common cancer in women with an estimated 570,000 new cases in 2018 and represents 6.6% of all cancers in women. About 90% of cervical cancer deaths occur in low- and middle-income countries. High mortality rates from cervical cancer globally can be reduced through a comprehensive approach that includes prevention, early diagnosis, effective screening and treatment programs. Cervical cancer can be prevented with primary prevention. Primary prevention is to prevent the occurrence of Human Papillomavirus (HPV) infection with the advantage of not causing side effects, easy and effective. This prevention can be done using screening methods that are easy and inexpensive to do, such as Visual Inspection of Acetic Acid (IVA), which is visual inspection with acetic acid. The purpose of this activity is to increase knowledge about early detection of cervical cancer, symptoms at an early and late stage in Cinere Depok District. The assessment of understanding can be seen from the results of the pre-test and post-test. The results of this activity show that people in Cinere Depok District have understood the socialization of early detection of cervical cancer and recognize the symptoms of early and late stages of cervical cancer with an increase in the average value of post-test, which is 90% of the pre-test score.